2016
DOI: 10.5472/mmjcr.2901.11
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of a progressively growing rectus sheath hematoma presented in a patient with chronic renal failure: A case report

Abstract: Introduction: Rectus sheath hematoma is a rare but an important clinical entity in the differential diagnosis of abdominal pain. It is often a self-limiting condition that can be managed successfully in conservative measures. If not recognized, it can lead to unnecessary emergency surgical procedures. A 55-year-old male patient suffering from chronic renal failure and cardiomyopathy presented with a progressively growing abdominal mass diagnosed to be a bilateral rectus sheath hematoma. Despite many complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…When the patient is hemodynamically stable, conservative management of RSH has been found to be the most effective treatment methodology due to the self-limiting nature of RSH [ 4 , 11 , 20 ]. Approximately 56-83% of the patients studied are successfully managed with CM alone [ 1 , 8 , 13 , 18 , 20 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…When the patient is hemodynamically stable, conservative management of RSH has been found to be the most effective treatment methodology due to the self-limiting nature of RSH [ 4 , 11 , 20 ]. Approximately 56-83% of the patients studied are successfully managed with CM alone [ 1 , 8 , 13 , 18 , 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a historical study, hematoma size has been suggested as a prognostic factor for surgery. RSH < 5 cm in diameter can be managed with CM while large RSH > 5 cm in diameters are managed with surgical intervention [ 4 , 13 ]. In the historical Klingler et al study, eight out of 23 patients had large RSH while 15 patients had small RSH.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations